Effect of Probiotics on Respiratory Infections in Stunted Preschool Children: A Quasi-Experimental Pre-Post Study - Deslina Rohmatul Luklu; Fajar Ari Nugroho; Annisa Rizky Maulidiana (Indonesian Journal of Human Nutrition, 2025)
Stunting in preschool-aged children increases susceptibility to upper respiratory tract infections (URTIs) due to impaired immune systems and imbalances in gut microbiota. This study aimed to evaluate the effect of probiotic supplementation on URTI incidence among stunted preschool-aged children and to support nutrition-based preventive strategies for reducing acute respiratory infections among vulnerable populations. This study used a quasi-experimental one-group pre-test-post-test design conducted over 120 days from August 2023 to January 2024. Fifteen stunted preschool-aged children enrolled in a kindergarten in Probolinggo City participated through total sampling. Data were collected using health status forms completed by enumerators during school days and by parents during holidays. Observations were conducted during two consecutive 60-day periods before and during probiotic supplementation. The intervention consisted of daily administration of 65 ml of a probiotic containing more than 100 million Lactobacillus casei Shirota strain bacteria per milliliter. Statistical analysis included Fisher’s Exact Test and the Wilcoxon Test with a significance level of p < 0.05. Results showed a significant difference in URTI status before and during probiotic supplementation (p = 0.042) and in the duration of school absenteeism (p = 0.011). However, no significant differences were found in URTI episode frequency, episode duration, or overall illness duration. The study concludes that probiotic supplementation (65 ml) has a significant impact on reducing URTI occurrence and school absenteeism in stunted preschool children.